An Assessment of Computer-Generated Stimuli for Use in Studies of Body Size Estimation and Bias - Alexi, Joanna; Dommisse, Kendra; Cleary, Dominique; Palermo, Romina; Kloth, Nadine; Bell, Jason (Frontiers in Psychology, 2019)
Inaccurate body size judgements are associated with body image disturbances, a clinical feature of many eating disorders. Accordingly, body related stimuli have become increasingly important in the study of estimation inaccuracies and body image disturbances. Technological advancements in the last decade have led to an increased use of computer generated (CG) body stimuli in body image research. However, recent face perception research has suggested that CG face stimuli are not recognised as readily and may not fully tap facial processing mechanisms. The current study assessed the effectiveness of using CG stimuli in an established body size estimation task (the ‘bodyline’ task). Specifically, we examined whether employing CG body stimuli alters body size judgments and associated estimation biases. One hundred and six 17- to 25-year-old females completed the CG bodyline task, which involved estimating the size of full-length CG body stimuli along a visual analogue scale. Our results show that perception of body size for CG stimuli was non-linear. Participants struggled to discriminate between extreme bodies sizes and overestimated the size change between near to average bodies. Furthermore, one of our measured size estimation biases was larger for CG stimuli. Our collective findings suggest using caution when employing CG stimuli in experimental research on body perception.